Odraz způsobu užití systému měření výkonnosti v podnikových finančních ukazatelích - Ladislav Šiška (Trendy v podnikání, 2015)
Simons (1995) seminal work identified two different purposes how the performance measurement systems (PMS) of the company can be used by managers. Diagnostic PMS use means monitoring organizational outcomes and correcting deviations from pre-set standards of performance. Interactive PMS use is associated with involvement of senior managers in the decision activities of their subordinates and thus stimulating learning and search for new opportunities of the future growth. The question is whether more diagnostically (or interactively) used PMSs mirror in the financial outcomes of the company, specifically in its returns and sales growth. To answer the question, the survey was carried out in companies domiciled in the Czech Republic. Applying exploratory factor analysis, the level of diagnostic and interactive PMS use in the company was distilled. Consecutively, the company's financial indicators of ROA, ROE, ROS and Sales growth were regressed on the identified factors of diagnostic and interactive PMS use. The results show that only diagnostic PMS use significantly influences ROE indicator and explains about 8 % of its fluctuations.